(untitled) (Research, Society and Development, 2023)
This article describes findings of an extensionist action of the Pharmacy course at the Vale do Rio Verde University Center (Unincor), which aimed to evaluate the sensitivity profile to the usual antimicrobials in the clinic in pregnant women with UTI in the municipality of Três Corações-MG. This research had as its target public the pregnant women assisted in the project Casulo of the institution of support Arca de Noé, in the municipality of Três Corações - MG, in which urine samples of the project participants were analyzed in search of cases suggestive of UTI, being taken into account parameters contained in the results of urinalysis, urine culture, identification of bacteria and antibiogram. This article presents the results of a study conducted with ten pregnant women, two of whom presented conditions suggestive of UTI. In view of the laboratory results obtained, it was observed that Escherichia coli (E. coli) was the uropathogen that appeared in both samples. In the antibiogram, Cefepime, Meropenem and Nitrofurantoin were antimicrobials with possibility of effectiveness against the isolated strains, unlike Norfloxacin, Ofloxacin, Cefaclor, Cephalotin and Imipenem. It was concluded that E. coli is the most frequent uropathogen among pregnant women and that for the effectiveness of antibiotic therapy, the uroculture must be performed together with the antibiogram, as well as the need to monitor empirical antibiotic therapy to evaluate the evolution of the treatment. From these results, it is important to educate health professionals, mainly prescribers, as well as users in relation to the topic addressed.